CONTINUITY OF CARE FOR PREGNANT WOMEN WITH A BREAST MILK DAM AT PRATAMA NIAR CLINIC, MEDAN AMPLAS DISTRICT, MEDAN CITY YEAR 2025 - Clara Maha Fretty Nainggolan; Situmorang, Tetti Seriati; Rumondang; Asnita Sinaga; Maswita Telaumbanua; Riani; Nur Ulya Sahlan, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
The ASI Dam is an event A the flow of venous blood vessels and lymph nodes is blocked, the flow of milk is blocked, and the pressure on the vessels and alveoli increases. Symptoms that often appear during breast milk dams include swollen breasts, breasts that feel hot and hard, breasts that feel painful when pressed, reddish breasts and mother's body temperature up to 38 C. If this continues, breast milk retention can occur, and it can also speed up the process of giving breast milk to mothers and children in a relaxed atmosphere. Make your room as comfortable as possible. Babies need breast milk every 2.5-3 hours for the first few weeks. By the end of the sixth week, most babies need milk every 4 hours. This program is good until babies are 10-12 months old. At this age, most babies sleep through the night, so there is no need to breastfeed at night (Ariandini 2023). In conclusion, education and intervention do the correct breastfeeding techniques and do breascare